2018
DOI: 10.1098/rsbl.2018.0197
|View full text |Cite
|
Sign up to set email alerts
|

Evolution in caves: selection from darkness causes spinal deformities in teleost fishes

Abstract: Only few fish species have successfully colonized subterranean habitats, but the underlying biological constraints associated with this are still poorly understood. Here, we investigated the influence of permanent darkness on spinal-column development in one species (Midas cichlid, ) with no known cave form, and one (Atlantic molly,) with two phylogenetically young cave forms. Specifically, fish were reared under a normal light : dark cycle or in permanent darkness (both species). We also surveyed wild-caught … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…We expected to find plastic changes in D/D reared SF involving pituitary and thyroid hormonal regulation, adipose tissue, and body shape based on the previous work on darkraised A. mexicanus SF, Chica CF, and Los Sabinos CF [47]. Furthermore, experiments on Poecillia mexicana, another teleost with cave adapted lineages, showed that darkness caused degenerate changes in the spine and promoted sexual isolation between adjacent surface and cave lineages [50][51][52]. Although our study was unable to replicate the changes in body shape seen by Rasquin (1949), we confirmed her observation of the increase of body fat.…”
Section: Discussionmentioning
confidence: 98%
“…We expected to find plastic changes in D/D reared SF involving pituitary and thyroid hormonal regulation, adipose tissue, and body shape based on the previous work on darkraised A. mexicanus SF, Chica CF, and Los Sabinos CF [47]. Furthermore, experiments on Poecillia mexicana, another teleost with cave adapted lineages, showed that darkness caused degenerate changes in the spine and promoted sexual isolation between adjacent surface and cave lineages [50][51][52]. Although our study was unable to replicate the changes in body shape seen by Rasquin (1949), we confirmed her observation of the increase of body fat.…”
Section: Discussionmentioning
confidence: 98%
“…Development of DD individuals was decelerated compared with LD individuals and the developmental lag increased over time and malformations of the spine accumulated (Figure 1). Several studies on fish under reduced illumination (Bolla & Holmefjord, 1988;Villamizar et al, 2011;Torres-Dowdall, Karagic, Plath, & Riesch, 2018). One potential explanation for the developmental lag in Midas cichlids is the inability to capture food in the dark environment.…”
Section: Development Is Decelerated In Dark-reared Midas Cichlidsmentioning
confidence: 99%
“…Extremophile species inhabiting environments with abiotic conditions lethal for most organisms, are of great interest to physiologists, ecologists and evolutionary biologists [1, 2]. These species offer valuable information on the limits of tolerance to abiotic conditions (e.g., [3]), on the process of adaptive divergence (e.g, [4]), and in the end, about the predictability of evolution (e.g., [5]). In fact, species inhabiting extreme ecological conditions have provided some very interesting cases of evolutionary convergence at different levels of biological organization, from molecular changes, to physiology, morphology, and performance [6, 7].…”
Section: Introductionmentioning
confidence: 99%